Enhancement of low-cycle fatigue life of high-nitrogen austenitic stainless steel at low strain amplitude through ultrasonic shot peening - Kumar C.S.; Chattopadhyay K.; Singh V.; Mahobia G.S. (My University, 2025)
Austenitic stainless steel stabilized by nitrogen has a very low content of undesired nickel (0.1 wt%). Such steel is a much better alternative for bioimplants than that stabilized with a high nickel content (≥ 8 wt%). For biomedical applications, in particular for orthopedic implants, resistance of the implant material to cyclic loading is an essential criterion. This investigation considers the effect of surface treatment by ultrasonic shot peening (USP) on low-cycle fatigue behavior, with 3 mm shots for varying durations of 3–18 min, at total strain amplitudes ranging from ±0.4% to ±0.8%. It was observed that, while the fatigue life was reduced due to USP at the highest strain amplitude of ±0.8%, it was enhanced by ≈ 18 times at the lowest strain amplitude of ±0.4% following 18 min of USP treatment. © 2020 Elsevier Ltd